Effect of Water Content on the Compressibility of Snow-Water Mixtures - Abele,Gunars; Haynes,F Donald (1979)
The stress-density relaionships of snow-water mixtures were investigated and are shown as functions of water content, initial snow density, initial snow-water mixture density and rate of deformation. An increase in water content in snow at a particular density or a decrease in the rate of deformation (or strain rate) decreases the stress, but apparently not the specific energy required to reach a specific mixture density. (Author)